Usage of solar over nuclear as an alternate energy source in support of Green & Sustainable supply chain practices in India (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Modernisation and industrialisation has provided materialistic benefits to mankind but in hindsight it has adversely impacted the environment. The major impacts have been on depletion of natural non-renewable sources, pollution in various forms and growing hazardous waste, which have eventually become a serious point of concern. As the whole world is eventually facing the threat of climate change, it is pertinent that some concrete & constructive steps are taken to neutralise or minimise these impacts. Over a few decades, there have been tangible initiatives being taken at global level, wherein, many countries across the globe have become sensitive to sustainability and have come together to set varieties of targets that have been put forth to control the negative side of industrialisation. Eventually it has been understood that we all will have to stand united for sustainability of our environment. Industrial expansion is driven by demand which in turn comes from innovation and availability of cost effective products. The demand from the end user finally drives the complete value stream of a product from cradle to grave. The management of this value stream is called supply chain management. The sustainability efforts to make the supply chain minimise environmental impacts is called the Greening of Supply Chain management (GSCM). We know that energy is a key ingredient in operationalisation of the supply chains and its inconsiderate use has a major impact on the environment. Energy is derived from both non-renewable as well as renewable resources and all have varying impacts on the environment. Hysterical use of easily available fossil fuels, which are non-renewable sources, is depleting the reserves and also because of their related heavy emission issues, are impacting the environment. The cautious use of energy and use of the right source is a big contributor in Greening of the Supply chain & long term sustainability. This paper looks at GSCM evolution, the role of energy in sustainability, introduces the various sources of energy & the related challenges. The special impetus in paper is given on nuclear as well as solar energy to highlights the specific benefits and downsides. It is derived that Solar energy made from Solar power, which is in abundance in India, is an alternate long term sustainable source.